Dampak Keterhubungan Ekonomi Global Terhadap Kinerja Keuangan Pemerintah di Negara-negara ASEAN - Ramadana, Sri Winarsih; Rahmaniar, Rahmaniar; Rizky, Fitrian (Universitas Teuku Umar, 2025)
This study investigates the impact of imports, exports, Foreign Direct Investment (FDI), and economic growth on the financial performance of governments in ASEAN countries. Utilizing secondary data from the Central Statistics Agency (BPS) and websites www.tradingeconomics.com and www.macrotrends.net, the study analyzes a census sample of all 10 ASEAN countries over the period 2015–2024, resulting in 100 panel data observations. The analysis employs panel data regression with Stata Version 17, supported by Chow, Hausman, and Lagrange Multiplier tests to ensure robustness. Findings reveal that FDI positively and significantly influences government financial performance, whereas economic growth has a significant but negative effect. Imports and exports were found to have no significant impact. These results underscore the importance of prioritizing foreign investment management and fiscal policy adaptation to address the complexities of economic growth while optimizing international trade dynamics in ASEAN countries. This study contributes empirical evidence to the literature by clarifying the distinct effects of key economic variables on government financial performance in ASEAN, offering implications for policy-making and economic governance.